Microbiological, antioxidant and physicochemical stability of a fruit and vegetable smoothie treated by high pressure processing and stored at room temperature - Fernandez, María Verónica; Denoya, Gabriela Inés; Jagus, Rosa Juana; Vaudagna, Sergio Ramon; Agüero, Maria Victoria (Elsevier, 2019)
This study aims to evaluate the physicochemical, antioxidant and microbiological stability of a fruit and vegetable smoothie treated with a previously optimized high pressure processing treatment (HPP: 630 MPa, 6min, 20 °C), stored at 25 °C. The control samples presented a significant increase in microbiological counts during the first days, while treated samples showed counts below the detection limit (<1.0 logCFU/g) throughout the 26 days of storage. Total soluble solids and pH did not change with treatment or along storage. Initially, HPP-treatment reduced pectinmethylestearase, peroxidase and polyphenoloxidase activities (PME, POD, PPO) by 83.9%, 31.4%, and 9.7%, respectively. During storage, PPO was maintained whereas POD decreased significantly on treated and control samples, while PME decreased on control, the slow value of treated ones was maintained. All the antioxidant indicators presented an initial increase in their values (5–75%) with treatment, presenting similar or better performance than control during storage. All samples presented initially a reddish color (a*: 12.4 ± 0.8) tending towards an orange-brownish color with storage time, probably due to the significant loss of betacyanin, smoothie's main red pigment. In conclusion, although adjustments are necessary to achieve pigments's stability, HPP-treatment is adequate to ensure the microbiological and antioxidant stability of the product at 25 °C.